2004
DOI: 10.1111/j.1365-2672.2004.02286.x
|View full text |Cite
|
Sign up to set email alerts
|

Stationary-phase acid and heat treatments for improvement of the viability of probiotic lactobacilli and bifidobacteria

Abstract: Aims: To investigate whether sublethal treatments of stationary-phase probiotic cultures enhance their survival during lethal treatments and to adapt these treatments to the fermenter-scale production of probiotic cultures. Methods and Results: Conditions for acid and heat pretreatments were screened for three Lactobacillus and two Bifidobacterium strains. Strains were sublethally treated both at laboratory scale and at fermenter scale in a strain-specific manner and exposed to a subsequent lethal treatment. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 30 publications
7
102
1
3
Order By: Relevance
“…For instance, it has been reported that stationary phase cells of L. rhamnosus yielded the highest recovery rate after drying (31-50 % survival), but early log-phase cells exhibited only14% survival and lag phase cells showed the highest susceptibility, with only a 2 % cell survival under similar conditions of drying (Corcoran et al, 2004). Saarela et al (2004) reported that freeze drying and storage stability performance of B. animalis subsp. lactis cells grown to a late-logarithmic growth phase (15 h) or to an early stationary phase.…”
Section: Important Parameters Affecting Microencapsulationmentioning
confidence: 99%
“…For instance, it has been reported that stationary phase cells of L. rhamnosus yielded the highest recovery rate after drying (31-50 % survival), but early log-phase cells exhibited only14% survival and lag phase cells showed the highest susceptibility, with only a 2 % cell survival under similar conditions of drying (Corcoran et al, 2004). Saarela et al (2004) reported that freeze drying and storage stability performance of B. animalis subsp. lactis cells grown to a late-logarithmic growth phase (15 h) or to an early stationary phase.…”
Section: Important Parameters Affecting Microencapsulationmentioning
confidence: 99%
“…By exhibiting stress conditions (pH, temperature, osmotic pressure etc) adaptive response can be provoked resulting in more desiccation-resistant bacterial cells (Abee and Wouters 1999;Baati et al 2000;Conrad et al 2000;Kim et al 2001;Saarela et al 2004;Morgan et al 2006). Response surface methodologies were reported to be particularly suitable to detect interactions and co-dependencies between the individual parameters mentioned (Schoug et al 2006).…”
Section: Residual Moisture Content (%)mentioning
confidence: 99%
“…For instance, the acid tolerance response has been evidenced in Bifidobacterium longum and B. animalis (32,41) and in other gram-positive bacteria such as Listeria monocytogenes (13), Enterococcus faecalis (16), or Lactococcus lactis (37). Mechanisms underlying acid tolerance used by gram-positive bacteria include not only proton pumping via the F 1 F o -ATPase but also changes in the cell membrane and regulatory mechanisms, alterations in different metabolic pathways, and amino acid decarboxylation (12).…”
mentioning
confidence: 99%